FAKTOR RISIKO LINGKUNGAN YANG BERHUBUNGAN DENGAN STUNTING PADA ANAK DI INDONESIA: LITERATUR REVIEW - Handoyo, Eko; Joko, Tri; Fitri, Yuni Pradilla (Jurnal Medikes (Media Informasi Kesehatan), 2023)
Stunting is a disorder of growth and development of children due to chronic malnutrition and recurrent infections, which is characterized by the length or height below the standard. Indonesia is included in the third country with the highest prevalence in the Southeast Asia region. The results of the 2018 Basic Health Research (Riskesdas) show that the prevalence of stunting in under-five children in Indonesia is 30.8%. In 2022, through the Indonesian Nutrition Status Survey (SSGI) the stunting prevalence in under-five children in Indonesia has decreased to 21.6%. The purpose of this study was to determine environmental risk factors for stunting. The method in this study uses the literature review method by selecting data sources according to the desired topics and criterias. The database used in the source search is google scholar and ejournal.undip.ac.id, with the keywords water, sanitation, hygiene, and stunting. The results of studies from 10 scientific journals on environmental risk factors for stunting show that water, sanitation and hygiene are risk factors for stunting.